AN ASSESSMENT OF THE SOCIO-ECONOMIC IMPACT OF WATER ACCESS FOR ROMA AND OTHER MARGINALIZED GROUPS IN RURAL SERBIA - Lebedinski, Lara; Djukić, Mihajlo; Pavlović, Dejana (Economics of Agriculture, 2025)
This paper uses survey data aiming to assess the socio economic impacts of providing water supply access to selected group of low-income communities in rural Serbia. Employing a mixed-methods approach, we have collected quantitative and qualitative data from beneficiaries of the water supply program to evaluate changes in quality of life, hygiene, nutrition, and new opportunities arising from reduced time spent on water collection. Results indicate that 94.6% of participants reported improvements in their quality of life, with an average satisfaction score of 8.8. Key benefits included enhanced hygiene and increased time for education and income-generating activities, though non-returnees exhibited higher satisfaction levels compared to returnees, highlighting persistent challenges for the latter group. The paper concludes that integrated strategies are essential to address both water access and broader socio-economic challenges. Recommendations for policymakers include the development of targeted interventions to improve infrastructure and support initiatives that facilitate employment and education.